SURVEI SARANA DAN PRASARANA PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SD NEGERI SEKECAMATAN RANTAU PANDAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The issues described above prompted researchers to conduct further studies on the actual condition of physical education facilities and infrastructure in public primary schools in the Rantau Pandan sub-district. This study was conducted to directly observe conditions in the field so that researchers could draw objective conclusions about the availability and suitability of physical education facilities in these schools. The main objective of this study was to obtain clear and accurate information about the facilities and infrastructure that support physical education learning activities in public elementary schools in the Rantau Pandan sub-district. This study used a quantitative descriptive approach, with a survey technique as the main method of describing the actual situation regarding the availability of sports facilities in schools. In this study, data sources were obtained from all public elementary schools in the Rantau Pandan Subdistrict, consisting of 10 elementary schools. The data collected includes information related to the number of facilities, their condition, and ownership status (owned, borrowed, or rented) of the facilities and infrastructure used for physical education activities. The results of the data analysis show that the utilisation rate of sports facilities and infrastructure in these schools is only 54% and 53.5%. This percentage indicates that the condition of the available facilities does not meet the standards of feasibility and ideal needs for physical education learning. Thus, it can be concluded that the availability of sports facilities and infrastructure in public elementary schools in the Rantau Pandan sub-district is still relatively low, with a feasibility rate of 54% and 53.5% categorised as unsuitable. These findings form an important basis for encouraging improvements in the quality of physical education facilities in the region.